Resin composition
The resin composition, featuring a propylene polymer, cellulose fibers, and maleic anhydride modified polyolefin wax, addresses the challenges of uniform dispersion and mechanical strength in conventional resin compositions by enhancing interface adhesion and flowability.
Patent Information
- Application Number
- JP2023529803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-16
- Filing Date
- 2022-06-07
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2042-06-07
AI Technical Summary
Conventional resin compositions containing cellulose fibers face challenges in achieving uniform dispersion, high mechanical strength, and processability, particularly with nano-sized cellulose fibers which tend to agglomerate due to their large surface area.
A resin composition comprising a propylene polymer, cellulose fibers, and a maleic anhydride modified polyolefin wax, where the maleic anhydride modified polyolefin wax acts as a compatibility agent to enhance the interface adhesion between the cellulose fibers and the propylene polymer, thereby improving dispersion and mechanical properties.
The proposed resin composition achieves uniform dispersion of cellulose fibers, resulting in enhanced mechanical strength and processability, while reducing the likelihood of agglomeration and improving the flowability of the resin.
Smart Images

Figure 0007657927000001 
Figure 0007657927000002 
Figure 0007657927000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a resin composition containing cellulose fibers. [Background technology]
[0002] Well-known cellulosic materials include natural materials such as wood flour, bamboo flour, and rice straw, and resins include thermoplastic resins such as polyethylene, polypropylene, and polystyrene. These resin compositions can be molded into desired shapes using various molding methods, such as extrusion and injection molding, and their practical application is being investigated, with the aim of effectively utilizing natural materials that have been discarded as industrial waste.
[0003] However, conventional resin compositions containing cellulose-based materials have limitations in use, such as poor moldability, particularly poor fluidity, when using small-sized cellulose fibers, and therefore are limited to use with large-sized cellulose-based materials, or the amount of cellulose-based material contained, etc. Therefore, in order to remove these limitations in use, various additives have been developed to improve the fluidity of resin compositions.
[0004] Patent Document 1 proposes the combined use of a specific polyolefin wax and a petroleum resin as a compatibilizer for cellulosic materials. Patent Document 2 proposes the use of a specific polyolefin wax containing a specific thermoplastic resin and having a molecular structure similar to that of the resin as a compatibilizer for cellulosic materials. Patent Documents 1 and 2 use wood flour with a large average particle size in the micron range as the cellulosic material. Patent Documents 3 and 4, on the other hand, use cellulose fibers with a small average fiber length in the nanometer range. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6470402 [Patent Document 2] Japanese Patent Application Publication No. 2020-111690 [Patent Document 3] Japanese Patent Publication No. 2020-12050 [Patent Document 4] Japanese Patent Publication No. 2020-76082 Summary of the Invention [Problem to be solved by the invention]
[0006] In any conventional resin composition, it is difficult to uniformly disperse wood flour or cellulose fibers, and there has been a demand for further improvement in their dispersibility. In addition, in recent years, there has been a demand for better dispersibility of nano-sized cellulose fibers in order to achieve higher mechanical strength and resistance to impact (impact resistance).
[0007] However, nano-sized cellulose fibers have a large surface area, making them difficult to dissolve in resins and prone to aggregation. This increases the torque of the resin composition during melt-kneading (reducing processability) and makes it difficult to obtain sufficient mechanical strength. To uniformly disperse nano-sized cellulose fibers, it is effective to weaken the hydrogen bonds between the cellulose fibers, and a compatibilizer is essential to make the cellulose fibers hydrophobic.
[0008] The present invention has been made in view of the above-mentioned problems, and specifically aims to provide a resin composition in which cellulose fibers are uniformly dispersed and which has high mechanical strength and processability, and a method for producing the resin composition. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a resin composition with a specific composition, thereby completing the present invention.
[0010] The present invention provides the following resin composition. [1] A propylene polymer (A), cellulose fibers (B), and a maleic anhydride-modified polyolefin wax (C) in which maleic anhydride is grafted onto a polyolefin wax, The propylene polymer (A) is contained in an amount of 50 to 99.8 parts by mass, the cellulose fiber (B) is contained in an amount of 0.1 to 49.9 parts by mass, and the maleic anhydride-modified polyolefin wax (C) is contained in an amount of 0.1 to 30 parts by mass, where the total amount of the propylene polymer (A), the cellulose fiber (B), and the maleic anhydride-modified polyolefin wax (C) is 100 parts by mass, The polyolefin wax is selected from the group consisting of ethylene homopolymers, copolymers of ethylene and an α-olefin having 3 to 12 carbon atoms, propylene homopolymers, and copolymers of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms; and The maleic anhydride-modified polyolefin wax (C) is a resin composition that satisfies the following (i) to (iv): (i) The number average molecular weight (Mn) of the polystyrene equivalent measured by gel permeation chromatography (GPC) is 300 to 20,000. (ii) The softening point measured in accordance with JIS K2207 is 70 to 160°C. (iii) Density measured by the density gradient tube method is 830 to 1000 kg / m 3 is (iv) The acid value is 30 to 200 mg KOH / g. [2] The resin composition according to [1], wherein the propylene polymer (A) is at least one selected from the group consisting of a propylene homopolymer, a propylene-ethylene copolymer, and a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms. [3] The resin composition according to [1] or [2], wherein the number average molecular weight (Mn) of the maleic anhydride-modified polyolefin wax (C) is 2,000 to 6,000. [4] The resin composition according to any one of [1] to [3], wherein the polyolefin wax is a propylene homopolymer or a propylene-ethylene copolymer. [5] The resin composition according to [4], wherein the polyolefin wax is a propylene homopolymer. [6] The resin composition according to any one of [1] to [5], wherein in the maleic anhydride-modified polyolefin wax (C), the number of maleic anhydride groups grafted to the polyolefin wax is 0.1 to 10 per molecule. [7] The resin composition according to any one of [1] to [5], wherein the maleic anhydride-modified polyolefin wax (C) has an acid value of 40 to 100 mgKOH / g. [8] The resin composition according to any one of [1] to [7], wherein the cellulose fibers (B) are cellulose nanofibers. [9] The resin composition according to any one of [1] to [7], wherein the mass ratio (C) / (B) of the maleic anhydride-modified polyolefin wax (C) to the cellulose fibers (B) is 0.01 to 0.2.
[0011] The present invention provides a resin composition in which cellulose fibers are uniformly dispersed and which has high mechanical strength and processability. DETAILED DESCRIPTION OF THE INVENTION
[0012] The present invention will be specifically described below. In the following description, the symbol "to" indicating a range of values means from above to below unless otherwise specified.
[0013] The present inventors have found that the use of a specific maleic anhydride-modified polyolefin wax (C) as a compatibilizer can improve the compatibility (interfacial adhesion) between the cellulose fibers (B) and the matrix resin, thereby suppressing aggregation of the cellulose fibers (B); and that this effect is particularly effective when a propylene-based polymer (A) is used as the matrix resin.
[0014] The reason for this is unclear, but is presumed to be as follows. Specifically, a specific maleic anhydride-modified polyolefin wax (C) having an acid value of at least a certain level (30 mgKOH / g or more), preferably a maleic anhydride-modified polypropylene wax having a low number-average molecular weight (Mn) (preferably 6000 or less), is not only able to adequately coat the surface of the cellulose fibers (B) having a large surface area, but also has excellent affinity with the propylene polymer (A) that is the matrix resin. Therefore, the cellulose fibers (B) and the matrix resin are sufficiently compatible (interfacial adhesion is enhanced), and aggregation of the cellulose fibers (B) can be suppressed, thereby achieving both mechanical strength and processability. The present invention will be described in detail below.
[0015] 1.Resin composition The resin composition of the present invention contains a propylene polymer (A), cellulose fibers (B), and a maleic anhydride-modified polyolefin wax (C).
[0016] When the total amount of the propylene polymer (A), cellulose fiber (B), and maleic anhydride-modified polyolefin wax (C) in the resin composition of the present invention is 100 parts by mass, the content of the propylene polymer (A) is 50 to 99.8 parts by mass, preferably 55 to 90 parts by mass, and more preferably 60 to 80 parts by mass. In order to obtain high processability, a high content of the propylene polymer (A) is preferred.
[0017] On the other hand, when the total amount of the propylene polymer (A), cellulose fiber (B), and maleic anhydride-modified polyolefin wax (C) in the resin composition is 100 parts by mass, the content of the cellulose fiber (B) is 0.1 to 49.9 parts by mass, preferably 5 to 45 parts by mass, and more preferably 10 to 40 parts by mass. In order to obtain high mechanical strength, a high content of the cellulose fiber (B) is preferred.
[0018] When the total amount of the propylene polymer (A), cellulose fiber (B), and maleic anhydride-modified polyolefin wax (C) in the resin composition is 100 parts by mass, the content of the maleic anhydride-modified polyolefin wax (C) is 0.1 to 30 parts by mass, preferably 0.5 to 20 parts by mass, and more preferably 1 to 10 parts by mass. In order to obtain high mechanical strength, a high content of the maleic anhydride-modified polyolefin wax (C) is preferred.
[0019] The mass ratio (C) / (B) of the maleic anhydride-modified polyolefin wax (C) to the cellulose fibers (B) is not particularly limited, but is preferably 0.01 to 0.2, more preferably 0.02 to 0.2, and even more preferably 0.05 to 0.15. When the mass ratio (C) / (B) is within the above range, the compatibility between the cellulose fibers (B) and the propylene polymer (A) is more likely to be improved, the interfacial adhesion between them is more likely to be improved, and the mechanical strength of the resin composition is also more likely to be increased.
[0020] The components and properties of the resin composition will be described below.
[0021] 1-1. Propylene polymer (A) The propylene polymer is a propylene (co)polymer. The propylene (co)polymer is preferably a propylene homopolymer or a copolymer of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms.
[0022] When the propylene polymer (A) is a copolymer of propylene and ethylene, the amount of propylene-derived structural units is preferably 60 to 99.5 mol%. The amount of propylene-derived structural units is preferably 80 to 99 mol%, more preferably 90 to 98.5 mol%, and even more preferably 95 to 98 mol%. The amount of ethylene-derived structural units is preferably 0.5 to 40 mol%, more preferably 1 to 20 mol%, even more preferably 1.5 to 10 mol%, and even more preferably 2 to 5 mol%. However, the total amount of propylene-derived structural units and the amount of ethylene-derived structural units is 100 mol%. When a propylene (co)polymer having a large amount of propylene-derived structural units is used, the heat resistance, appearance, and mechanical strength of the resulting molded article are improved.
[0023] When the propylene-based polymer (A) is a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms, examples of the α-olefin having 4 to 12 carbon atoms include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. Among these, 1-butene is particularly preferred. The propylene-α-olefin copolymer may further contain structural units derived from an olefin other than those having 4 to 12 carbon atoms, such as a small amount, e.g., 10 mol % or less, of structural units derived from ethylene. On the other hand, when no structural units derived from ethylene are contained, the resulting molded article tends to have a particularly good balance between heat resistance and mechanical strength. The propylene (co)polymer may contain only one α-olefin, or two or more α-olefins may be used in combination.
[0024] In the propylene-C4-C12 α-olefin copolymer, the amount of propylene-derived structural units is preferably 60 to 90 mol%, more preferably 65 to 88 mol%, even more preferably 70 to 85 mol%, and particularly preferably 75 to 82 mol%. The amount of carbon atom-containing α-olefin-derived structural units is preferably 10 to 40 mol%, more preferably 12 to 35 mol%, even more preferably 15 to 30 mol%, and particularly preferably 18 to 25 mol%. The total amount of propylene-derived structural units and carbon atom-containing α-olefin-derived structural units is 100 mol%.
[0025] When the composition of the propylene-C4-C12 α-olefin copolymer is within the above range, molded articles with excellent appearance are obtained. While the reason for this is unclear, this composition slows down the crystallization rate, lengthening the flow time of the resin composition in the mold or during the cooling process. As a result, it is thought that the surface tends to be smooth. Furthermore, when the composition is within the above range, the mechanical strength and heat resistance of the resulting molded articles are good.
[0026] The melting point (Tm) of the propylene-C4-C12 α-olefin copolymer measured by differential scanning calorimetry (DSC) is preferably 60 to 120°C, more preferably 65 to 100°C, and even more preferably 70 to 90°C.
[0027] The stereoregularity of the propylene polymer (A) is not particularly limited, but it preferably has a substantially syndiotactic structure. For example, when the propylene polymer (A) has a substantially syndiotactic structure, the entanglement point molecular weight (Me) decreases at the same molecular weight, resulting in increased molecular entanglement. This increases the melt tension and reduces the risk of dripping. Furthermore, when a molded article is produced using a resin composition containing the propylene polymer (A), the polymer adheres appropriately to a mold or roll. Furthermore, compared with a typical propylene (co)polymer having an isotactic structure, the propylene polymer (A) having a syndiotactic structure has a slower crystallization rate, which allows for slower cooling in a mold or roll, improving adhesion. As a result, it is believed that the surface gloss of the molded article is enhanced, as well as improved abrasion resistance, scratch resistance, impact resistance, and the like.
[0028] The propylene polymer (A) having a substantially syndiotactic structure means that 13 This means that the peak area corresponding to 19.5 to 20.3 ppm in a C-NMR spectrum is 0.5% or more relative to the total peak area detected. When the syndiotacticity is within the above range, the crystallization rate is sufficiently slow, resulting in very good processability. Furthermore, a propylene-based (co)polymer in which the propylene-derived structural unit has a substantially syndiotactic structure has much better abrasion resistance and scratch resistance than general-purpose polyolefin-based resins such as polyethylene, block polypropylene, and isotactic polypropylene. The propylene-based polymer (A) having a syndiotactic structure can be produced by various known production methods.
[0029] The ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the propylene polymer (A) measured by gel permeation chromatography (GPC) is not particularly limited, but is preferably 6.0 or less. Mw / Mn is more preferably 4.0 or less, and even more preferably 3.0 or less. When Mw / Mn is within the above range, the amount of low-molecular-weight components that cause deterioration of physical properties is small, resulting in excellent appearance, heat resistance, and mechanical strength. Furthermore, the amount of high-molecular-weight components that cause an increase in melt viscosity during kneading is small, resulting in excellent processability. Both the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are determined in terms of polystyrene.
[0030] The melting point (Tm) of the propylene polymer (A) measured by a differential scanning calorimeter (DSC) is preferably 250°C or lower, or is not observed. If a melting point is observed, the upper limit of the melting point is more preferably 230°C, even more preferably 200°C, and particularly preferably 170°C. The lower limit of the melting point is preferably 50°C, more preferably 70°C, even more preferably 90°C, particularly preferably 130°C, and more preferably 150°C. When the melting point is within the above range, smoke, odor, etc. are unlikely to occur during preparation of the resin composition by melt kneading or during production of a molded article by melt molding. Furthermore, a molded article that is unlikely to become sticky and has an excellent balance of heat resistance, mechanical strength, impact strength, and impact absorption can be obtained.
[0031] The glass transition temperature (Tg) of the propylene polymer (A) measured by a differential scanning calorimeter (DSC) is preferably −140 to 50° C., more preferably −120 to 20° C., and even more preferably −100 to −10° C. When the glass transition temperature is within the above range, the resulting molded article has a good balance of long-term stability, heat resistance, impact resistance, and mechanical strength.
[0032] The density of the propylene polymer (A), measured according to the density gradient tube method in accordance with ISO 1183, is 800 to 1800 kg / m 3 The lower limit of the density is preferably in the range of 810 kg / m 3More preferably, 830 kg / m 3 is more preferable, and 860 kg / m 3 is particularly preferred, and 900 kg / m 3 The upper limit of the density is more preferably 1300 kg / m 3 More preferably, 1290 kg / m 3 is more preferable, and 1270 kg / m 3 is particularly preferred, and 1240 kg / m 3 More preferably, 1200 kg / m 3 is more preferable.
[0033] The flexural modulus of the propylene polymer (A), measured in accordance with JIS K7171:94 (ISO 178), is preferably 1 to 10,000 MPa. When the flexural modulus is 500 MPa or higher, it is preferably 500 to 7,000 MPa, more preferably 700 to 5,000 MPa, particularly preferably 900 to 3,000 MPa, and even more preferably 1,000 to 2,300 MPa. When the flexural modulus is within the above range, not only is the processability of the resin composition excellent, but the resulting molded article also exhibits good scratch resistance, heat resistance, and mechanical strength. When the flexural modulus is less than 500 MPa, it is preferably less than 300 MPa, more preferably less than 100 MPa, and even more preferably less than 50 MPa. A flexural modulus within the above range not only provides excellent flexibility, but also provides molded articles with excellent impact absorption, light weight, vibration resistance, vibration damping, and sound damping. Furthermore, molded articles with excellent design properties, such as mold transferability and texture transferability, and excellent surface grip can be obtained.
[0034] 1-2. Cellulose fiber (B) The cellulose fiber (B) can be mixed with the propylene polymer (A) and the maleic anhydride-modified polyolefin wax (C), and is not particularly limited as long as it can provide the desired appearance and physical properties. Examples of the cellulose fiber (B) include cellulose fiber and cellulose nanofiber. The resin composition may contain only one type of cellulose fiber (B), or two or more types. Depending on the purpose, wood flour may be used instead of the cellulose fiber (B).
[0035] The average fiber length of the cellulose fibers (B) (single fibers) is preferably 0.001 to 5 mm. When the average fiber length is 0.001 mm or more, the mechanical strength of the molded article is easily improved, and when the average fiber length is 5 mm or less, the dispersibility of the cellulose fibers (B) is less likely to be impaired. From the same viewpoint, the average fiber length of the cellulose fibers (B) is more preferably 0.01 to 3 mm. When the cellulose fibers (B) are aggregated, the average fiber length of the aggregates may also be the same as above.
[0036] The average fiber diameter of the cellulose fibers (B) (single fibers) is preferably 10 μm or less, more preferably 5 μm or less. The lower limit of the average fiber diameter (single fibers) is not particularly limited, but may be, for example, 10 nm. When the cellulose fibers (B) are aggregated, the average fiber diameter of the aggregates is preferably 2 mm or less, more preferably 1 mm or less.
[0037] The average fiber length and average fiber diameter of the cellulose fibers (B) can be determined by measuring the fiber lengths (or fiber diameters) of any 100 cellulose fibers from image data of a resin composition (e.g., an injection-molded test piece) taken with a scanning electron microscope (SEM), and averaging these values to determine the average fiber length (or average fiber diameter).
[0038] Such cellulose fibers (B) can be obtained by treating a cellulose-containing raw material selected from wood, pulp, paper, plant stems and leaves, and plant shells with a pulverizer. Specifically, the cellulose-containing raw material is coarsely pulverized using a cutting machine such as a shredder, and then treated with an impact pulverizer or extruder, or dried. Then, the mixture is stirred using a media pulverizer to obtain finely divided cellulose fibers.
[0039] For example, cellulose fibers can be obtained by cutting raw pulp, treating it with hot water at 100°C or higher to hydrolyze and weaken the hemicellulose portion, and then defibrating it using a pulverizing method using a high-pressure homogenizer, microfluidizer, ball mill, disc mill, etc.
[0040] As the cellulose fiber (B), cellulose fibers made from such cellulose pulp or modified cellulose fibers can be used. Among these, modified cellulose fibers are preferred in terms of stability, performance, etc.
[0041] Modified cellulose fibers include those modified with one or more modifying agents selected from an esterifying agent, a silylating agent, an isocyanate compound, a halogenated alkylating agent, an alkylene oxide and / or a glycidyl compound.
[0042] Examples of the esterifying agent include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of a plurality of these arbitrarily selected therefrom, as well as In addition, examples of the anhydrides include symmetric anhydrides (acetic anhydride, maleic anhydride, cyclohexane-carboxylic anhydride, benzene-sulfonic anhydride), mixed acid anhydrides (butyric-valeric anhydride), cyclic anhydrides (succinic anhydride, phthalic anhydride, naphthalene-1,8:4,5-tetracarboxylic dianhydride, cyclohexane-1,2,3,4-tetracarboxylic 3,4-anhydride), ester acid anhydrides (acetic 3-(ethoxycarbonyl)propanoic anhydride, benzoylethyl carbonate), and the like, which are arbitrarily selected from these.
[0043] The silylating agent includes a Si-containing compound having at least one reactive group capable of reacting with the hydroxyl groups on the surface of the cellulose fibers or with the groups after hydrolysis thereof.
[0044] Examples of silylating agents include chlorodimethylisopropylsilane, chlorodimethylbutylsilane, chlorodimethyloctylsilane, chlorodimethyldodecylsilane, chlorodimethyloctadecylsilane, chlorodimethylphenylsilane, chloro(1-hexenyl)dimethylsilane, dichlorohexylmethylsilane, dichloroheptylmethylsilane, trichlorooctylsilane, hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, 1,3-divinyl-1,3-diphenyl-1,3-dimethyldisilazane, 1,3-N-dioctyltetramethyldisilazane, diisobutylsilane, and the like. Examples of the silane include butyl tetramethyldisilazane, diethyl tetramethyldisilazane, N-dipropyl tetramethyldisilazane, N-dibutyl tetramethyldisilazane, 1,3-di(para-t-butylphenethyl)tetramethyldisilazane, N-trimethylsilylacetamide, N-methyldiphenylsilylacetamide, N-triethylsilylacetamide, t-butyldiphenylmethoxysilane, octadecyldimethylmethoxysilane, dimethyloctylmethoxysilane, octylmethyldimethoxysilane, octyltrimethoxysilane, trimethylethoxysilane, and octyltriethoxysilane.
[0045] The halogenated alkylating agent may be an organic compound having at least one functional group capable of reacting with the hydroxyl groups on the surface of the cellulose fibers to halogenated alkylate them.
[0046] Examples of halogenated alkylating agents that can be used include chloropropane, chlorobutane, bromopropane, bromohexane, bromoheptane, iodomethane, iodoethane, iodooctane, iodooctadecane, iodobenzene, etc. Among these, bromohexane and iodooctane are preferred in terms of reactivity, stability, cost, etc.
[0047] The isocyanate compound may be an organic compound having at least one isocyanate group capable of reacting with the hydroxyl groups on the surface of the cellulose fiber. The isocyanate compound may also be a blocked isocyanate compound in which the blocking group is released at a specific temperature to regenerate the isocyanate group, or may be a dimer or trimer of polyisocyanate, a modified product such as biuretized isocyanate, or polymethylene polyphenyl polyisocyanate (polymeric MDI).
[0048] Examples of the isocyanate compound include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, araliphatic polyisocyanates, blocked isocyanate compounds, and polyisocyanates. For example, tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, 3-methylpentane-1,5-diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane), tolylene diisocyanate (TDI), 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate Examples of the blocking agent include methyl isocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, α,α,α,α-tetramethylxylylene diisocyanate, and blocked isocyanate compounds obtained by reacting the above-mentioned isocyanate compounds with an oxime-based blocking agent, a phenol-based blocking agent, a lactam-based blocking agent, an alcohol-based blocking agent, an active methylene-based blocking agent, an amine-based blocking agent, a pyrazole-based blocking agent, a bisulfite-based blocking agent, or an imidazole-based blocking agent. Among these, TDI, MDI, hexamethylene diisocyanate, and blocked isocyanates made from modified hexamethylene diisocyanate and hexamethylene diisocyanate are preferably used in terms of reactivity, stability, cost, etc.
[0049] The alkylene oxide and / or glycidyl compound can be an organic compound having at least one alkylene oxide group, glycidyl group, and / or epoxy group capable of reacting with hydroxyl groups on the surface of the cellulose nanofibers.
[0050] Examples of alkylene oxides and / or glycidyl compounds include glycidyl ethers such as methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, 2-methyloctyl glycidyl ether, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, sec-butylphenyl glycidyl ether, n-butylphenyl glycidyl ether, phenylphenol glycidyl ether, cresyl glycidyl ether, and dibromocresyl glycidyl ether; glycidyl esters such as glycidyl acetate and glycidyl stearate; ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether; Examples of suitable glycidyl ethers include polyhydric alcohol glycidyl ethers such as glycerol ether, 1,4-butanediol diglycidyl ether, hexamethylene glycol diglycidyl ether, resorcinol diglycidyl ether, bisphenol A diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, sorbitol polyglycidyl ether, sorbitan polyglycidyl ether, polyglycerol polyglycidyl ether, and diglycerol polyglycidyl ether. Among these, 2-methyloctyl glycidyl ether, hexamethylene glycol diglycidyl ether, and pentaerythritol tetraglycidyl ether are preferred from the standpoints of reactivity, stability, cost, and the like.
[0051] 1-3. Maleic anhydride modified polyolefin wax (C) The maleic anhydride-modified polyolefin wax (C) can function as a compatibilizer to facilitate compatibility between the propylene polymer (A) and the cellulose fiber (B), although the maleic anhydride-modified polyolefin wax (C) is different from the propylene polymer (A).
[0052] As mentioned above, simply blending cellulose fibers (B) with the propylene-based polymer (A) that forms the base of a resin composition can result in poor dispersibility of the cellulose fibers (B), making it difficult to knead them uniformly. In particular, if the blending ratio of cellulose fibers (B) relative to the propylene-based polymer (A) is high or if the specific surface area of the cellulose fibers (B) is large, the viscosity increases during kneading, making dispersion difficult. Therefore, when molding the resin composition, processability is reduced and the molded product tends to lack uniformity. As a result, insufficient mechanical strength can be obtained, and the molded product may have poor appearance, or may have insufficient heat resistance and flexibility (elongation).
[0053] In response to this, the inventors have conducted research and have found that by blending a specific maleic anhydride-modified polyolefin wax (C) having an acid value of a certain level or more, which is obtained by modifying a polyolefin wax with maleic anhydride, when kneading a propylene polymer (A) with cellulose fibers (B), a resin composition having good appearance, heat resistance, mechanical strength, flexibility, and processability can be obtained.
[0054] Although the detailed mechanism is unclear, the presence of carboxyl groups in the molecular chain of the maleic anhydride-modified polyolefin wax (C) electrically interacts with the hydroxyl groups present in the molecules of the cellulose fiber (B), enhancing their affinity. Furthermore, the polyolefin wax portion of the maleic anhydride-modified polyolefin wax (C) has good compatibility with the propylene-based polymer (A). Therefore, the cellulose fiber (B) and the propylene-based polymer (A) are compatible with each other via the maleic anhydride-modified polyolefin wax (C), making it easier for the cellulose fiber (B) to be uniformly dispersed in the propylene-based polymer (A). This is thought to result in reduced friction during kneading and improved fluidity of the resin composition. Furthermore, improved fluidity of the resin composition improves processability and the appearance of the molded product. Furthermore, the improved fluidity of the resin composition reduces the likelihood of structural destruction of the cellulose fibers (B) or their aggregates, and reduces the likelihood of voids forming at the interface between the cellulose fibers (B) and the propylene polymer (A) (improved interfacial adhesion), making it easier to obtain sufficient mechanical strength. These effects are particularly easily achieved by using a maleic anhydride-modified polypropylene wax with a relatively low number-average molecular weight (Mn).
[0055] 1-3-1. Structure / physical properties The maleic anhydride-modified polyolefin wax (C) is a polyolefin wax grafted with maleic anhydride. The polyolefin wax constituting the maleic anhydride-modified polyolefin wax (C) can be a polyethylene wax (ethylene homopolymer, copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms) or a propylene wax (propylene homopolymer, copolymer of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms) from the viewpoint of easily obtaining affinity with the propylene polymer (A). Among them, a propylene wax is preferred, and a propylene homopolymer is more preferred, from the viewpoint of increasing affinity with the propylene polymer (A).
[0056] The maleic anhydride modified polyolefin wax (C) preferably satisfies the following requirements (i) to (iv).
[0057] (i) The number-average molecular weight (Mn) of the maleic anhydride-modified polyolefin wax (C) measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 300 to 20,000. The upper limit of the number-average molecular weight (Mn) is more preferably 15,000, even more preferably 10,000, even more preferably 6,000, and particularly preferably 5,000. The lower limit of the number-average molecular weight (Mn) is more preferably 500, even more preferably 700, especially preferably 1,000, and even more preferably 2,000. When the number-average molecular weight of the maleic anhydride-modified polyolefin wax (C) is within the above range, the dispersibility of the cellulose fibers (B) in the resin composition is improved, resulting in improved appearance and mechanical strength of the resulting molded article. The processability of the resin composition is also improved. In particular, when the number average molecular weight is 6000 or less (preferably 2000 to 6000), the molecular size is small and the surface of the cellulose fiber (B) having a large surface area can be sufficiently coated, which makes it easier to further improve dispersibility and processability of the resin composition.
[0058] The number average molecular weight (Mn) of the maleic anhydride-modified polyolefin wax (C) can be decreased by increasing the polymerization temperature during polymerization of the unmodified polyolefin wax (described later) or by increasing the hydrogen concentration during polymerization. It can also be adjusted by the amount of catalyst used during polymerization of the unmodified polyolefin wax or by purification after polymerization.
[0059] Furthermore, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the maleic anhydride-modified polyolefin wax (C) measured by gel permeation chromatography (GPC) is not particularly limited, but is preferably 9.0 or less, more preferably 8.0 or less, and even more preferably 7.0 or less. When Mw / Mn is within the above range, there is little low-molecular-weight component that would cause a decrease in physical properties, so that the appearance, heat resistance, mechanical strength, etc. of the molded article obtained from the resin composition are good. The weight average molecular weight (Mw) is also a polystyrene-equivalent value.
[0060] The Mw / Mn of the maleic anhydride-modified polyolefin wax (C) can be adjusted by the catalyst type and polymerization temperature during polymerization of the unmodified polyolefin wax. Ziegler-Natta catalysts and metallocene catalysts are generally used for polymerization of unmodified polyolefin waxes, but to achieve the desired Mw / Mn, it is preferable to use a metallocene catalyst. The Mw / Mn of the maleic anhydride-modified polyolefin wax (C) can also be adjusted by refining the unmodified polyolefin wax.
[0061] (ii) The softening point of the maleic anhydride-modified polyolefin wax (C), measured according to JIS K2207, is preferably 70 to 160°C. The upper limit of the softening point is more preferably 155°C, and even more preferably 150°C. The lower limit is more preferably 90°C, and even more preferably 110°C. When the softening point is equal to or lower than the upper limit, the processability of the resin composition and the appearance, heat resistance, and mechanical strength of the resulting molded article are improved. In particular, a lower softening point is preferable because the maleic anhydride polyolefin wax (C) melts more easily before other components (e.g., the propylene polymer (A)) during melt-kneading, and the surface of the cellulose fiber (B) is more easily coated. When the softening point is equal to or higher than the lower limit, bleeding out of the maleic anhydride-modified polyolefin wax (C) in the resulting resin composition is more easily suppressed.
[0062] The softening point of the maleic anhydride-modified polyolefin wax (C) can be adjusted by the composition of the unmodified polyolefin wax. For example, when the unmodified polyolefin wax described below is a copolymer of ethylene and an α-olefin, the softening point can be lowered by increasing the content of the α-olefin. The softening point can also be adjusted by the catalyst type and polymerization temperature during preparation of the unmodified polyolefin wax, or by purification after polymerization.
[0063] (iii) The density of the maleic anhydride modified polyolefin wax (C), measured by the density gradient tube method in accordance with JIS K7112, is 830 to 1000 kg / m 3 More preferably, it is 860 to 980 kg / m 3 and more preferably 890 to 960 kg / m 3 When the density of the maleic anhydride-modified polyolefin wax (C) is within the above range, the dispersibility of the cellulose fibers (B) is improved, and the appearance and mechanical strength of the resulting molded article are improved. In addition, the processability of the resin composition is also improved.
[0064] The density of the maleic anhydride-modified polyolefin wax (C) can be adjusted by the composition of the unmodified polyolefin wax, the polymerization temperature during polymerization, the hydrogen concentration, and the like, which will be described later.
[0065] (iv) The acid value derived from maleic anhydride in the maleic anhydride-modified polyolefin wax (C) is preferably 30 to 200 mgKOH / g, more preferably 30 to 150 mgKOH / g, even more preferably 30 to 120 mgKOH / g, even more preferably 40 to 100 mgKOH / g, and particularly preferably 40 to 90 mgKOH / g. When the acid value derived from maleic anhydride in the maleic anhydride-modified polyolefin wax (C) is equal to or greater than the lower limit, compatibility between the maleic anhydride-modified polyolefin wax (C) and the cellulose fiber (B) tends to be improved. When the acid value is equal to or less than the upper limit, excessive interaction that can cause an increase in viscosity, etc., tends to be suppressed. This improves the processability of the resin composition, and further improves the balance between the appearance, heat resistance, and mechanical strength of the resulting molded article.
[0066] The acid value derived from maleic anhydride can be determined by titration, elemental analysis, or NMR. Specifically, the acid value can be measured in accordance with JIS K5902.
[0067] (v) In the maleic anhydride-modified polyolefin wax (C), the number of maleic anhydride groups grafted to the polyolefin wax is preferably, for example, 0.1 to 10 per molecule. When the number of maleic anhydride groups is within the above range, the compatibility between the propylene polymer (A) and the cellulose fiber (B) is easily improved without excessively increasing the torque during melt-kneading of the resin composition. The number of maleic anhydride groups can be calculated from the number-average molecular weight (Mn) and the acid value.
[0068] The number of maleic anhydride groups grafted per molecule can be adjusted by, for example, the acid value or the number average molecular weight (Mn).
[0069] 1-3-2. Manufacturing method The maleic anhydride-modified polyolefin wax (C) is obtained by modifying a polyolefin wax (unmodified polyolefin wax) with maleic anhydride.
[0070] Hereinafter, the unmodified polyolefin wax and the method for preparing it will be explained first, and then the method for preparing the maleic anhydride-modified polyolefin wax using the unmodified polyolefin wax will be explained.
[0071] (Unmodified polyolefin wax) The unmodified polyolefin wax is preferably a polyethylene-based wax or a propylene-based wax.
[0072] Polyethylene wax The polyethylene wax is preferably the polyethylene wax described in JP-A-2009-144146, etc., which will be briefly described below.
[0073] The polyethylene wax may be, for example, an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms. Specific examples of the ethylene homopolymer include high-density polyethylene wax, medium-density polyethylene wax, low-density polyethylene wax, and linear low-density polyethylene wax.
[0074] When the polyethylene wax is a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms, the amount of structural units derived from ethylene is preferably 91.0 to 99.9 mol%, more preferably 93.0 to 99.9 mol%, even more preferably 95.0 to 99.9 mol%, and particularly preferably 95.0 to 99.0 mol%. On the other hand, the amount of structural units derived from an α-olefin having 3 or more carbon atoms is preferably 0.1 to 9.0 mol%, preferably 0.1 to 7.0 mol%, even more preferably 0.1 to 5.0 mol%, and particularly preferably 1.0 to 5.0 mol%. However, the total of the structural units derived from ethylene and the structural units derived from an α-olefin having 3 or more carbon atoms is 100 mol%. The proportion of structural units in the polyethylene wax is 13 It can be determined by analyzing the C-NMR spectrum.
[0075] Examples of α-olefins having 3 to 12 carbon atoms that can be copolymerized with ethylene include linear or branched α-olefins such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. Preferred are propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. More preferred are α-olefins having 3 to 8 carbon atoms, particularly preferred are propylene and 1-butene, and even more preferred is propylene. Copolymerization of ethylene with propylene or 1-butene tends to harden the maleic anhydride-modified polyolefin wax (C) and reduce stickiness. This improves the surface properties of the resulting molded article. This is also preferred in terms of increasing the mechanical strength and heat resistance of the resulting molded article. The reason for this is unclear, but compared to other α-olefins, propylene and 1-butene lower their melting points more efficiently with a small amount of copolymerization. Therefore, compared to other α-olefins with the same melting point, the degree of crystallinity tends to be higher, which is presumably the reason. The α-olefin copolymerized with ethylene can be used alone or in combination of two or more.
[0076] Polypropylene wax The polypropylene wax is a propylene homopolymer, a copolymer of propylene and ethylene, or a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms.
[0077] When the polypropylene wax is a copolymer of propylene and ethylene, the content of propylene-derived structural units is preferably 60 to 99.5 mol%. The amount of propylene-derived structural units is more preferably 80 to 99 mol%, even more preferably 90 to 98.5 mol%, and particularly preferably 95 to 98 mol%. The amount of ethylene-derived structural units is preferably 0.5 to 40 mol%, more preferably 1 to 20 mol%, even more preferably 1.5 to 10 mol%, and particularly preferably 2 to 5 mol%. However, the total of the propylene-derived structural units and the ethylene-derived structural units is 100 mol%. Using such a polypropylene wax makes it easy to obtain a molded product that has an excellent balance of appearance, mechanical strength, and heat resistance.
[0078] When the polypropylene wax is a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms, examples of the α-olefin having 4 to 12 carbon atoms include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. Of these, 1-butene is particularly preferred.
[0079] In the propylene-C4-C12 α-olefin copolymer, the amount of propylene-derived structural units is preferably 60 to 90 mol%, more preferably 65 to 88 mol%, even more preferably 70 to 85 mol%, and particularly preferably 75 to 82 mol%. The amount of structural units derived from α-olefins having 4 or more carbon atoms is preferably 10 to 40 mol%, more preferably 12 to 35 mol%, even more preferably 15 to 30 mol%, and particularly preferably 18 to 25 mol%, provided that the total of the propylene-derived structural units and the structural units derived from α-olefins having 4 or more carbon atoms is 100 mol%.
[0080] Among these, polypropylene waxes are preferred, propylene homopolymers or copolymers of propylene and ethylene are more preferred, and propylene homopolymers are even more preferred. system The maleic anhydride-modified wax has higher compatibility with the propylene polymer (A), and the molded article obtained has a good balance of appearance, mechanical strength, and heat resistance. In addition, the processability of the resin composition is also good.
[0081] Method for preparing unmodified polyolefin wax The unmodified polyolefin wax may be obtained by directly polymerizing ethylene, propylene, 4-methyl-1-pentene, etc., or by thermally decomposing a high molecular weight (co)polymer. The thermal decomposition is preferably carried out at 300 to 450°C for 5 minutes to 10 hours. In this case, unsaturated terminals are generated in the unmodified polyolefin wax. 1 When the number of vinylidene groups (unsaturated terminals) per 1000 carbon atoms measured by H-NMR is 0.5 to 5, the affinity between the propylene polymer (A) and the cellulose fiber (B) tends to be increased. The unmodified polyolefin wax may be purified by solvent fractionation, which separates the wax based on the difference in solubility in a solvent, or by distillation.
[0082] On the other hand, when an unmodified polyolefin wax is obtained by directly polymerizing ethylene, propylene, 4-methyl-1-pentene, or the like, the method is not limited thereto, and various known production methods can be applied, for example, ethylene or the like may be polymerized using a Ziegler-Natta catalyst or a metallocene catalyst.
[0083] ·Preparation method of maleic anhydride modified polyolefin wax (C) The maleic anhydride-modified polyolefin wax (C) is obtained by modifying the unmodified polyolefin wax with maleic anhydride.
[0084] The method for modification with maleic anhydride is not particularly limited. For example, it may be a method of melt-kneading raw material unmodified polyolefin wax and maleic anhydride in the presence of a polymerization initiator such as an organic peroxide. Alternatively, it may be a method of adding a polymerization initiator such as an organic peroxide to a solution obtained by dissolving raw material unmodified polyolefin wax and maleic anhydride in an organic solvent, and melt-kneading the solution.
[0085] For melt kneading, known devices such as an autoclave, a Henschel mixer, a V-type blender, a tumbler blender, a ribbon blender, a single-screw extruder, a multi-screw extruder, a kneader, a Banbury mixer, etc. can be used. Among these, the use of a device with excellent batch-type melt kneading performance, such as an autoclave, allows the production of a maleic anhydride-modified polyolefin wax (C) in which each component is uniformly dispersed and reacted. Furthermore, compared with the continuous method, the batch method is preferable in that it is easier to adjust the residence time and can secure a longer residence time, making it relatively easy to increase the modification rate and modification efficiency.
[0086] In addition, after modifying the unmodified polyolefin wax with maleic anhydride, it may be processed in accordance with the manufacturing method of the resin composition. For example, the maleic anhydride-modified polyolefin wax (C) may be processed into a powder, tablet, or block shape. Alternatively, the maleic anhydride-modified polyolefin wax (C) may be dispersed or dissolved in water or an organic solvent. The method for dissolving or dispersing the maleic anhydride-modified polyolefin wax (C) in water or an organic solvent is not particularly limited. For example, the maleic anhydride-modified polyolefin wax (C) may be dissolved or dispersed by stirring. Alternatively, it may be heated while stirring.
[0087] Furthermore, the maleic anhydride-modified polyolefin wax (C) may be microparticulated by dissolving or dispersing it in water or an organic solvent and then precipitating it. Examples of methods for microparticulating the maleic anhydride-modified polyolefin wax (C) include the following: First, the solvent composition is adjusted so that the maleic anhydride-modified polyolefin wax (C) precipitates at 60 to 100°C. Then, a mixture of the solvent and the maleic anhydride-modified polyolefin wax (C) is heated to dissolve or disperse the maleic anhydride-modified polyolefin wax (C) in the solvent. Then, the solution is cooled at an average cooling rate of 1 to 20°C / hour (preferably 2 to 10°C / hour) to precipitate the maleic anhydride-modified polyolefin wax (C). Furthermore, a poor solvent may then be added to further promote the precipitation.
[0088] 1-4.Optional ingredients The resin composition of the present invention may further contain optional components as long as the objects and effects of the present invention are not impaired. Examples of optional components include flame retardants such as brominated bisphenols, brominated epoxy resins, brominated polystyrene, brominated polycarbonates, triphenyl phosphate, phosphonic acid amides, and red phosphorus; flame retardant synergists such as antimony trioxide and sodium antimonate; heat stabilizers such as phosphate esters and phosphites; antioxidants such as hindered phenols; heat resistance agents; weathering agents; light stabilizers; mold release agents; flow modifiers; colorants; lubricants; antistatic agents; crystal nucleating agents; plasticizers; and foaming agents.
[0089] The content of the optional components in the resin composition of the present invention is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less, per 100 parts by mass of the total of the propylene polymer (A), the cellulose fiber (B), and the maleic anhydride polyolefin wax (C).
[0090] 2. Manufacturing method of resin composition The resin composition of the present invention can be produced by various methods. For example, the propylene polymer (A), cellulose fibers (B), maleic anhydride polyolefin wax (C), and optional components may be mixed simultaneously or in any order using a tumbler, V-blender, Nauta mixer, Banbury mixer, kneading roll, single-screw or twin-screw extruder, or the like. The resin composition of the present invention may also be produced by melt-kneading the propylene polymer (A), cellulose fibers (B), maleic anhydride polyolefin wax (C), and optional components, and then diluting the mixture with the propylene polymer (A).
[0091] Alternatively, the cellulose fibers (B) may be impregnated with the maleic anhydride polyolefin wax (C) and then mixed with the propylene polymer (A). The method for impregnating the cellulose fibers (B) with the maleic anhydride polyolefin wax (C) is not particularly limited. For example, the cellulose fibers (B) may be brought into contact with the molten maleic anhydride polyolefin wax (C), and tension may be applied to the cellulose fibers (B) using a roll or bar, or the cellulose fibers (B) may be repeatedly expanded and bundled, or pressure or vibration may be applied to the cellulose fibers (B). These methods allow the maleic anhydride polyolefin wax (C) to penetrate deep into the cellulose fibers (B).
[0092] 3.Applications The resin composition of the present invention can be molded into a molded article by, for example, injection molding, blow molding, inflation molding, cast film molding, extrusion molding such as profile extrusion molding, compression molding, etc. Among these molding methods, injection molding is preferred from the viewpoints of design and moldability.
[0093] The resin composition of the present invention is used to manufacture molded articles for a wide range of applications, from household goods to industrial products. Examples of applications include electrical and electronic components, automotive parts, mechanical components, food containers, films, sheets, and fibers. Specific examples include office and office equipment such as printers, personal computers, word processors, keyboards, PDAs (personal digital assistants), telephones, mobile phones, smartphones, tablet devices, Wi-Fi routers, facsimiles, copiers, ECRs (electronic cash registers), calculators, electronic organizers, electronic dictionaries, cards, holders, and stationery; home appliances such as washing machines, refrigerators, vacuum cleaners, microwave ovens, lighting fixtures, game consoles, irons, and kotatsu tables; audiovisual equipment such as TVs, VTRs, video cameras, digital cameras, single-lens reflex cameras, portable audio devices, radio-cassette players, tape recorders, minidiscs, CD players, speakers, and liquid crystal displays; and electrical and electronic components and communication equipment such as connectors, relays, capacitors, switches, printed circuit boards, coil bobbins, semiconductor encapsulation materials, electric wires, cables, transformers, deflection yokes, distribution boards, and clocks.
[0094] Examples of uses also include automobile, vehicle, ship, aircraft and construction materials such as seats (padding, outer material, etc.), belts, ceiling coverings, convertible tops, armrests, door trims, rear package trays, carpets, mats, sun visors, wheel covers, tires, mattress covers, airbags, insulation materials, hand straps, hand straps, wire covering materials, electrical insulation materials, paints, coating materials, upholstery materials, flooring materials, corner walls, deck panels, covers, plywood, ceiling boards, partition boards, side walls, carpets, wallpaper, wall coverings, exterior materials, interior materials, roofing materials, soundproofing boards, heat insulating boards, window materials, etc.; and lifestyle and sporting goods such as clothing, curtains, sheets, plywood, synthetic fiber boards, rugs, entrance mats, sheets, buckets, hoses, containers, eyeglasses, bags, cases, goggles, skis, rackets, tents, musical instruments, etc.
[0095] Further examples of uses include bottles for shampoo, detergent, cosmetics, etc.; seasoning bottles for cooking oil, soy sauce, etc.; beverage bottles for mineral water, juice, etc.; heat-resistant food containers such as lunch boxes and chawanmushi bowls; tableware such as plates and chopsticks; various other food containers; packaging films, packaging bags, toothbrush and knife handles, etc.
[0096] Among these, it is particularly suitable for applications requiring mechanical strength, such as automobile parts. [Example]
[0097] The present invention will be described in detail based on examples, but the present invention is not limited to these examples.
[0098] 1. Resin Propylene polymer (A): PP manufactured by Prime Polymer Co., Ltd. (trade name J107G, MFR 30 g / 10 min, density 910 kg / m 3 ) was used. High-density polyethylene (for comparison): Prime Polymer HDPE (product name 7000F, MFR 0.04 g / 10 min, density 950 kg / m 3 ) was used. These physical properties were measured under the following conditions.
[0099] <mfr> Measurement was performed in accordance with JIS K7210 at 230°C under a load of 2.16 kg.
[0100] <density> Measurement was carried out in accordance with JIS K7112.
[0101] 2. Cellulose fiber The mechanically crushed crude pulp and water were placed in a pressure-resistant autoclave and heated at 130°C for 5 hours to obtain refined pulp. The refined pulp was then beaten using a disc refiner, defibrated using a high-pressure homogenizer (internal pressure: 100 MPa), and dried in a hot air oven to obtain cellulose fiber (B) (cellulose nanofiber).
[0102] When the obtained cellulose fibers (B) were observed using image data obtained by a scanning electron microscope (SEM), the aggregates of the cellulose fibers (B) had an average fiber diameter of 1 mm and an average fiber length of 2 to 3 mm.
[0103] 3. Compatibilizer 3-1. Preparation of maleic anhydride modified polyolefin wax (C) [Manufacturing Example 1] The maleic anhydride-modified polyolefin wax (W1) was prepared according to (1) to (3).
[0104] (1) Preparation of catalyst In a 1.5-liter glass autoclave, 25 g of commercially available anhydrous magnesium chloride was suspended in 500 ml of hexane. The suspension was maintained at 30°C, and 92 ml of ethanol was added dropwise over 1 hour while stirring, allowing the reaction to proceed for 1 hour. Subsequently, 93 ml of diethylaluminum monochloride was added dropwise over 1 hour, allowing the reaction to proceed for another 1 hour. After that, 90 ml of titanium tetrachloride was added dropwise, and the reaction vessel was heated to 80°C and allowed to react for 1 hour. The solid portion was then washed with hexane by decantation until no free titanium was detected. The solid (catalyst) was then suspended in hexane, and the titanium concentration was determined by titration. The suspension was then used to prepare unmodified polyolefin wax.
[0105] (2) Preparation of unmodified polyolefin wax A 2-liter stainless steel autoclave, the atmosphere of which had been thoroughly replaced with nitrogen, was charged with 930 ml of hexane and 70 ml of propylene, and hydrogen was pumped in at 20.0 kg / cm. 2 Next, the temperature inside the system was raised to 170°C, and then 0.1 mmol of triethylaluminum, 0.4 mmol of ethylaluminum sesquichloride, and a hexane suspension of the catalyst obtained by the above method were injected with ethylene so that the amount of titanium component was 0.008 mmol in atomic terms, and polymerization was initiated.
[0106] Then, the total pressure was increased to 40 kg / cm by continuously supplying only ethylene. 2 The pressure was maintained at 170°C (gauge pressure) and polymerization was carried out for 40 minutes at 170°C. A small amount of ethanol was then added to the system to terminate the polymerization, and unreacted ethylene and propylene were purged. The resulting polymer solution was dried overnight at 100°C under reduced pressure to obtain an unmodified polyolefin wax.
[0107] (3) Maleic anhydride modification of unmodified polyolefin wax 200 g of the unmodified polyolefin wax obtained by the above method was placed in a glass reactor and melted at 170°C under a nitrogen atmosphere. Next, 10 g of maleic anhydride and 2.2 g of di-t-butyl peroxide (hereinafter also referred to as "DTBPO") were continuously fed to the reaction system (temperature 170°C) over 5 hours. After heating and reacting for 1 hour, the molten product was degassed for 0.5 hours under a vacuum of 10 mmHg to remove volatiles. The reaction product was then cooled to obtain maleic anhydride-modified polyolefin wax (C1).
[0108] [Manufacturing Example 2] A maleic anhydride-modified polyolefin wax (C2) was prepared in the same manner as in Production Example 1, except that the amounts of di-t-butyl peroxide and maleic anhydride to be reacted were adjusted to change the Mn and acid value as shown in Table 1.
[0109] [Manufacturing Example 3] A maleic anhydride-modified polyolefin wax (C3) was prepared in the same manner as in Production Example 1, except that di-t-butyl peroxide was adjusted and Mn was changed as shown in Table 1.
[0110] [Manufacturing Example 4] A maleic anhydride-modified polyolefin wax (C4) was prepared in the same manner as in Production Example 1, except that di-t-butyl peroxide was adjusted and Mn was changed as shown in Table 1.
[0111] [Manufacturing Example 5] An unmodified polyolefin wax was prepared by adjusting the amounts of ethylene and propylene. The unmodified polyolefin wax was then modified with maleic anhydride in the same manner as in Production Example 1, except that the amounts of di-t-butyl peroxide and maleic anhydride were adjusted so as to obtain the acid value shown in Table 1, thereby preparing a maleic anhydride-modified polyolefin wax (C5).
[0112] [Manufacturing Example 6] PP manufactured by Prime Polymer (product name J107G, MFR 30g / 10min, density 910kg / m 3 ) was placed in an autoclave and heated at 380°C for 3 hours under a nitrogen atmosphere to prepare an unmodified polyolefin wax. Thereafter, the unmodified polyolefin wax was modified with maleic anhydride in the same manner as in Production Example 1 to prepare a maleic anhydride-modified polyolefin wax (C6).
[0113] [Manufacturing Example 7] PP manufactured by Prime Polymer (product name J107G, MFR 30g / 10min, density 910kg / m 3 ) was placed in an autoclave and heated at 380°C for 2 hours under a nitrogen atmosphere to prepare an unmodified polyolefin wax. Thereafter, the unmodified polyolefin wax was modified with maleic anhydride in the same manner as in Production Example 1 to prepare a maleic anhydride-modified polyolefin wax (C7).
[0114] [Manufacturing Example 8] An unmodified polyolefin wax was prepared in the same manner as in Production Example 1, except that only ethylene was supplied as a polymerization component. Thereafter, the unmodified polyolefin wax was modified with maleic anhydride in the same manner as in Production Example 1, to prepare a maleic anhydride-modified polyolefin wax (C8).
[0115] 3-2. Preparation of comparative polyolefin wax [Manufacturing Example 9] An unmodified polyolefin wax (W1) was prepared in the same manner as in Production Example 1, except that the polymerization degrees of propylene and ethylene were adjusted.
[0116] [Manufacturing Example 10] An unmodified polyolefin wax (W2) was prepared in the same manner as in Production Example 1, except that the polymerization degrees of propylene and ethylene were adjusted.
[0117] [Manufacturing Example 11] An unmodified polyolefin wax (W3) was prepared in the same manner as in Production Example 1, except that the polymerization degrees of propylene and ethylene were adjusted.
[0118] [Manufacturing Example 12] PP manufactured by Prime Polymer (product name J107G, MFR 30g / 10min, density 910kg / m 3 ) was placed in an autoclave and heated at 380°C for 2 hours under a nitrogen atmosphere to prepare an unmodified polyolefin wax. Thereafter, the unmodified polyolefin wax was modified with maleic anhydride in the same manner as in Production Example 1 to prepare a maleic anhydride-modified polyolefin wax (W4).
[0119] [Manufacturing Example 13] A maleic anhydride-modified polyolefin wax (W5) was prepared in the same manner as in Production Example 12, except that the amounts of di-t-butyl peroxide and maleic anhydride to be reacted were adjusted to change the Mn and acid value as shown in Table 1.
[0120] [Manufacturing Example 14] A maleic anhydride-modified polyolefin wax (W6) was prepared in the same manner as in Production Example 12, except that the amounts of di-t-butyl peroxide and maleic anhydride to be reacted were adjusted to change the Mn and acid value as shown in Table 1.
[0121] 3-3. Measurement of physical properties The physical properties of the maleic anhydride modified polyolefin waxes (C1) to (C8) and the comparative polyolefin waxes (W1) to (W6) were measured by the following methods.
[0122] <Composition> The amount of each structural unit constituting the wax (composition ratio of ethylene and propylene) was measured under the following conditions: 13 It was determined by analyzing the C-NMR spectrum. · 13 C-NMR measurement conditions Equipment: Bruker Biospin AVANCEIII cryo-500 nuclear magnetic resonance spectrometer Measurement nuclei: 13 C(125MHz) Measurement mode: Single pulse proton broadband decoupling Pulse width: 45° (5.00 μsec) Number of points: 64k Measurement range: 250 ppm (-55 to 195 ppm) Repeat time: 5.5 seconds Number of times accumulated: 128 Measurement solvent: orthodichlorobenzene / benzene-d6 (4 / 1 (volume ratio)) Sample concentration: 60 mg / 0.6 mL Measurement temperature: 120℃ Window function: exponential (BF: 1.0 Hz) Chemical shift reference: δδ signal 29.73 ppm
[0123] <Number average molecular weight (Mn)> The number average molecular weight (Mn) was determined by GPC measurement under the following conditions. The number average molecular weight (Mn) was then determined from a calibration curve using commercially available monodisperse standard polystyrene. Apparatus: Gel permeation chromatograph Alliance GPC2000 (Waters) Solvent: o-dichlorobenzene Columns: TSKgel GMH6-HT x 2, TSKgel GMH6-HTL columns x 2 (both manufactured by Tosoh Corporation) Flow rate: 1.0ml / min Sample: 0.15 mg / mL o-dichlorobenzene solution Temperature: 140℃
[0124] <Softening point> Measurement was carried out in accordance with JIS K2207.
[0125] <density> Measurement was carried out in accordance with JIS K7112.
[0126] <Acid value> Measurement was carried out in accordance with JIS K5902.
[0127] <Number of maleic anhydride groups per molecule> The number of maleic anhydride groups grafted per molecule was calculated from the number average molecular weight (Mn) and the acid value.
[0128] The measurement results are shown in Table 1. [Table 1]
[0129] 4. Preparation of Resin Composition [Example 1] 67 parts by mass of a propylene polymer (A), 30 parts by mass of cellulose fibers (B), and 3 parts by mass of a maleic anhydride-modified polyolefin wax (C1) were melt-kneaded using a co-rotating twin-screw extruder HK25D (manufactured by Parker Corporation: φ25 mm, L / D=41), and extruded at a cylinder temperature of 210°C to obtain a pelletized resin composition.
[0130] [Examples 2 to 13 and Comparative Examples 1 to 10] Resin compositions were obtained in the same manner as in Example 1, except that the types and amounts of the components to be blended were changed so as to obtain the compositions shown in Table 2 or 3.
[0131] 5. Evaluation of resin composition The resin compositions of Examples 1 to 13 and Comparative Examples 1 to 10 were evaluated as follows.
[0132] <torque> The resulting resin composition was pelletized using a twin-screw extruder, and the steady torque was measured and the average value was calculated. The pellets were then evaluated according to the following criteria. ◎: Average torque less than 10 N m ○: Average torque is 10 N·m or more and less than 11 N·m △: Average torque is 11N·m or more but less than 12N·m ×: Average torque is 12 N m or more
[0133] <Tensile strength, tensile modulus> The resulting resin composition pellets were dried at 120°C for 8 hours and then injection molded using an injection molding machine (Niigata NN100, manufactured by Niigata Machine Techno Co., Ltd.) under conditions of a cylinder temperature of 210°C, a screw rotation speed of 60 rpm, an injection pressure of 130 MPa, and a mold temperature of 60°C to prepare test specimens. The shape of the test specimens conformed to JIS K7161. Then, using the injection-molded test pieces (ISO universal test pieces), tensile tests were carried out based on JIS K7161 under conditions of a chuck distance of 115 mm and a test speed of 50 mm / min, to measure the tensile strength and tensile modulus.
[0134] The tensile strength was evaluated based on the following criteria. ◎: Tensile strength is 35 MPa or more ○: Tensile strength is 30 MPa or more and less than 35 MPa △: Tensile strength is 25 MPa or more and less than 30 MPa ×: Tensile strength less than 25 MPa
[0135] The tensile modulus was evaluated based on the following criteria. ◎: Tensile modulus of elasticity is 2200 MPa or more ○: Tensile modulus of elasticity is 2000 MPa or more and less than 2200 MPa △: Tensile modulus of elasticity is 1800 MPa or more and less than 2000 MPa ×: Tensile strength less than 1800 MPa
[0136] <Interfacial adhesion> The cross section of the resulting resin composition pellet was observed under a scanning electron microscope (SEM) at 1000x magnification, and the interfacial adhesion between the cellulose fiber (B) and the resin was evaluated according to the following criteria. ○: 95% or more of the entire interface is in contact △: 90% to less than 95% of the entire interface is in contact ×: Less than 90% of the entire interface is in contact
[0137] The evaluation results of Examples 1 to 13 are shown in Table 2, and the evaluation results of Comparative Examples 1 to 10 are shown in Table 3. If all of the above evaluations were fair or better, it was judged to be within the acceptable range.
[0138] [Table 2]
[0139] [Table 3]
[0140] As shown in Table 2, the resin compositions of Examples 1 to 13, which contain a propylene polymer (A), cellulose fibers (B), and a specific maleic anhydride-modified polyolefin wax (C), are all excellent in both processability and mechanical strength.
[0141] In contrast, the resin compositions of Comparative Examples 1, 8, and 9, which did not contain a compatibilizer, and the resin compositions of Comparative Examples 2 and 3, which used an unmodified olefin wax as a compatibilizer, all had low tensile strength, and the resin composition of Comparative Example 4 had low torque and tensile strength. This is thought to be because the cellulose fibers and the resin were not compatible with each other, resulting in the formation of voids at the interface between them.
[0142] On the other hand, the resin compositions of Comparative Examples 5 to 7, which used an acid-modified olefin wax with a high number-average molecular weight (Mn) as a compatibilizer, all showed a significant increase in torque and poor processability. Furthermore, even when a specific acid-modified olefin wax (C1) was used, if the resin was high-density polyethylene, no interfacial adhesion was obtained, and no improvement in strength or processability was observed (Comparison between Comparative Example 10 and Example 1).
[0143] This application claims priority from Japanese Patent Application No. 2021-100340, filed June 16, 2021. The contents of the specification and drawings of that application are incorporated herein by reference in their entirety. [Industrial Applicability]
[0144] The resin composition of the present invention has cellulose fibers uniformly dispersed therein and has high mechanical strength and processability, making it suitable for a variety of applications.< / mfr>
Claims
1. The present invention relates to a propylene-based polymer (A), cellulose fibers (B), and a maleic anhydride-modified polyolefin wax (C) in which maleic anhydride is grafted onto a polyolefin wax, The propylene-based polymer (A) is contained in an amount of 50 to 99.8 parts by mass, the cellulose fiber (B) is contained in an amount of 0.1 to 49.9 parts by mass, and the maleic anhydride-modified polyolefin wax (C) is contained in an amount of 0.1 to 30 parts by mass, where the total amount of the propylene-based polymer (A), the cellulose fiber (B), and the maleic anhydride-modified polyolefin wax (C) is 100 parts by mass, The cellulose fiber (B) is a cellulose nanofiber, The polyolefin wax is a polypropylene-based wax selected from the group consisting of propylene homopolymers and copolymers of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms; and The maleic anhydride modified polyolefin wax (C) satisfies the following (i) to (iv): Resin composition. (i) The number average molecular weight (Mn) of the polymer in terms of polystyrene measured by gel permeation chromatography (GPC) is 300 to 7,500. (ii) The softening point measured in accordance with JIS K2207 is 70 to 160°C. (iii) A density measured by a density gradient tube method is 830 to 1000 kg / m 3 is (iv) The acid value is 30 to 200 mgKOH / g.
2. The propylene polymer (A) is at least one selected from the group consisting of a propylene homopolymer, a propylene-ethylene copolymer, and a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms. The resin composition according to claim 1.
3. The number average molecular weight (Mn) of the maleic anhydride modified polyolefin wax (C) is 2000 to 6000. The resin composition according to claim 1.
4. The polyolefin wax is a propylene homopolymer. The resin composition according to claim 1.
5. The acid value of the maleic anhydride modified polyolefin wax (C) is 40 to 100 mgKOH / g. The resin composition according to claim 1.
6. The acid value of the maleic anhydride modified polyolefin wax (C) is 40 to 60 mgKOH / g. The resin composition according to claim 1.
7. In the maleic anhydride-modified polyolefin wax (C), the number of maleic anhydride groups grafted to the polyolefin wax is 0.1 to 10 per molecule. The resin composition according to claim 1.
8. The mass ratio (C) / (B) of the maleic anhydride modified polyolefin wax (C) to the cellulose fiber (B) is 0.01 to 0.
2. The resin composition according to claim 1.
Citation Information
Patent Citations
Polyolefin composition
JP1988033446A
Drying for pressed flower
JP1989070402A
Polyolefin-vegetable fiber-based composition for molding
JP1996283475A
Polyolefin composition and its molded article
JP2005187524A
Resin composition
JP2020012050A